Concept of al-amanah (trustworthiness) and al-mas'uliyyah (responsibility) for human's character from ethical Islamic perspective - Shuhari, Mohd Hasrul; Hamat, Mohd Fauzi; Basri, Muhammad Nasri Hassan; Wan Khairuldin, Wan Mohd Khairul Firdaus; Wahab, Muhammad Rashidi; Engku Alwi, Engku Ahmad Zaki; Mamat, Akila (Allied Business Academies, 2019)
Al-Amanah (trusts) and al-mas'uliyyah (responsibilities) refer to the ethical character of the human character that must be practiced in daily life, especially by every Muslim. Both of these noble qualities will help someone avoid something that can cause him to be regarded as a badly-touted individual. This article will discuss the concept of al-Amanah (trustworthiness) and al-mas'uliyyah (responsibility) according to the ethical Islamic perspective. This article analyzes the thoughts of several Islamic scholars such as al-Ghazali (505H) and several exegetes (mufassirin) in understanding the two terms through their works. Finally, this study concludes that the concept of al-amanah (trust) and al-mas'uliyyah (responsibility) is capable of creating the quality of human character among Muslim individuals according to the ethical Islamic perspective. © 2019, Allied Business Academies.